Creep properties and permeability evolution in triaxial rheological tests of hard rock in dam foundation - Xu, Wei-ya; Wang, Ru-bin; Wang, Wei; Zhang, Zhi-liang; Zhang, Jiu-chang; Wang, Wen-yuan (Journal of Central South University, 2012)
Triaxial creep tests were carried out under seepage pressure by using rock servo-controlled triaxial rheology testing equipment. Based on experimental results, rock rheological properties influenced by seepage-stress coupling were studied, and variations of seepage rate with time in complete creep processes of rock were analyzed. It is shown that, when the applied stress is less than failure stress level, the creep deformation is not obvious, and its main form is steady-state creep. When applied stress level is greater than or less than but close to fracture stress, it is easier to see the increase of creep deformation and the more obvious accelerative creep characteristics. The circumferential creep deformation is obviously higher than the axial creep deformation. At the stage of steady-state creep, the average of seepage flow rate is about 4.7×10 −9 m/s at confining pressure ( σ 3 ) of 2 MPa, and is about 3.9×10 −9 m/s at σ 3 of 6 MPa. It is seen that the seepage flow rate at σ 3 of 2 MPa in this case is obviously larger than that at σ 3 of 6 MPa. At the stage of creep acceleration, the seepage flow rate is markedly increased with the increase of time. The variation of rock permeability is directly connected to the growth and evolution of creep crack. It is suggested that the permeability coefficient in complete creep processes of rock is not a constant, but is a function of rock creep strain, confining pressure, damage variable and pore water pressure. The results can be considered to provide a reliable reference for the establishment of rock rheological model and parameter identification.